Trading in Crowded Markets - Kyle, Albert S.; Obizhaeva, Anna A.; Wang, Yajun (Journal of Financial and Quantitative Analysis, 2026)
Abstract We study trading among strategic traders who may incorrectly assess the degree of market crowdedness. These mistakes distort equilibrium strategies and prices. When traders underestimate market crowdedness, they target larger inventories and trade more aggressively, but their actual profits are lower than expected because they underestimate the amount of information already impounded in prices. Crowded markets are prone to abrupt crashes. The magnitude of price dislocations and the speed of recovery during fire-sale events can help infer traders’ beliefs about market crowdedness.